Penerapan Fmea untuk Mengurangi Tes Ulang pada Proses Pengujian Vitamin D di Laboratorium Pengujian PT. Tüv Nord Indonesia - Fajar Sidiq Firdaus (Syntax Corporation Indonesia, 2024)
The purpose of this study is to analyze quality control in vitamin D testing using FMEA and fishbone diagrams. The type of research is applied research with a population in the form of retest data on vitamin D testing at PT TUV NORD Indonesia during the period January – December 2023. From the results of the pareto chart there are 6 causes of retest, then the highest percentage is analyzed using a fishbone diagram. Next, it was analyzed with FMEA to determine the priority scale so that the largest RPN value was obtained, namely not carrying out routine blender maintenance with a value of 245. And a 5W+1H analysis was carried out, so a proposal for improvement was obtained at the highest RPN value, namely carrying out maintenance planning on the equipment periodically.